NASIONALISME BURUH DALAM SEJARAH INDONESIA - Yuliati, Dewi (Faculty of Humanities, Diponegoro University, 2012)
ABSTRACT The state and the workers have close relationship, because the state is a political unity between the folks (includes the workers) and the government as the states’ administrator. In the context of industrial relationship, there often takes place interest differences between the state and the workers, and this condition can rises conflict between these two parties. Generally, the workers are judged as the marginal party who struggle only for the economical reasons, without any thinking of political stability. This research shows that this point of view is not exactly true, because the workers really dare to search justice and prosperity for the folks. This research concludes that the workers movement can be the inspiration to strengthen the Indonesian nationalism. Keywords: labour nationalism, Sarekat Islam Semarang, Internationale